Study of knowledge, attitude and practice regarding patient education in hypertension among community pharmacists in China - Lei Chen; Yueyue Liu; Xiaoyu Xi (BMC, 2022)
Abstract Background In the prevention and treatment of hypertension, patient education is an important measure to improve the awareness rate and control rate of patients. The professional and geographical advantages of community pharmacists enable them to play an important role in the patient education in hypertension. The purpose of this study was to understand the situation of patient education in hypertension conducted in Chinese community pharmacies, and put forward measures according to the problems. Methods A multi-stage competitive sampling by convenience was used to select community pharmacists working in community pharmacies in China for the study. Based on KAP theory, the first draft of the questionnaire was designed and the Delphi method was used to improve the questionnaire and a pre-study was conducted to test the reliability of the questionnaire. In January 2020, electronic questionnaires were distributed to 143 community pharmacists in Chinese community pharmacies. SPSS24 software was used for descriptive statistics and subgroup analysis of data. Results One hundred and eight valid questionnaires were collected, and the efficiency rate was 75.5%. Most of the respondents were younger than 30 years old (98.1%), and had bachelor's degree (95.4%). In terms of knowledge, only 15.7% considered themselves "very good" and even 10.2% considered themselves "very bad". Only 35%-55% of respondents answered correctly for patient education content that requires more specialized knowledge, such as treatment and medication. Respondents generally had a positive attitude on the effect of hypertension patient education, but slightly less recognition of their role in patient education. In terms of practice, programs related to patient education have been conducted to different degrees. More than 30% of the community pharmacists interviewed implemented them occasionally or never. Conclusions Despite a positive attitude, most of the respondents did not have a high level of knowledge or practice. In China, more research evidence and new guidelines are needed to emphasize the importance and responsibilities of community pharmacists. Continuing education should be certificated at the national level and meet the various needs of community pharmacists. And salary incentives can be tried to motivate them.